2014
DOI: 10.1155/2014/481508
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Biodeterioration Enzymatic Activities of Fungal Contamination Isolated from Some Ancient Yemeni Mummies Preserved in the National Museum

Abstract: Sophisticated mummification using chemical preservation was prevalent in ancient Yemeni civilization as noted in the 4th century B.C. mummies of the National Museum of Yemen, Sana'a, used in this study. Five of these mummies were used to evaluate hydrolytic enzymes produced as a result of fungal contamination. Forty-seven fungal species were isolated, thereby reflecting a high degree of contamination which may have resulted from the poor ventilation and preservation system. Aspergillus was the most common genu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…6 Fig). U. chartarum is well known to be involved in biodeterioration of organic and inorganic substrates; it can invade surfaces containing very little substrate, thus posing a risk of degradation for various materials, including cultural artifacts [42,43]. In our study, U. chartarum demonstrated growth inside CD agar and mock layers (S9 and S11 Figs), suggesting its possible role in biodeterioration of tempera painting.…”
Section: Plos Onesupporting
confidence: 53%
“…6 Fig). U. chartarum is well known to be involved in biodeterioration of organic and inorganic substrates; it can invade surfaces containing very little substrate, thus posing a risk of degradation for various materials, including cultural artifacts [42,43]. In our study, U. chartarum demonstrated growth inside CD agar and mock layers (S9 and S11 Figs), suggesting its possible role in biodeterioration of tempera painting.…”
Section: Plos Onesupporting
confidence: 53%
“…The most prevalent genus was Cladosporium . Of the nine identified genera, Aspergillus , Chaetomium, Cladosporium , Penicillium , and Trichoderma are reported as common microbiota in ancient works of art 1 , 2 , 17 , 30 , 31 . The actin region was sequenced to confirm the results obtained with the ITS region, and to classify to species level some samples that could not be done with ITS.…”
Section: Resultsmentioning
confidence: 99%
“…Assay of the cellulase activity showed that 95% of the samples produce extracellular enzymes that break down cellulose into smaller oligosaccharides or monosaccharides, as evident from the clear zone observed after staining the plates with Gram’s iodine (see Table 2 and Supplementary Figure S4 ). This fraction that includes the two new species (sample #19: Periconia epilithographicola and sample #21: Coniochaeta cipronana ) also comprehends species of Arthrinium, Aspergillus, Chaetomium, Cladosporium, Colletotrichum, Penicillium , and Trichoderma , being the first four commonly reported with cellulolytic activity 31 , 39 45 . These observations are congruent with the habitat of restricted carbon sources, in which sheets or laminae made of fibers of cellulose pulp were the support material for the growth of microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the cultivation strategy, this hydrolytic group, isolated from the mummy surface, is composed of members of the genera Bacillus , Micrococcus , Alternaria , Cladosporium , Penicillium and of the species A. pullulans and E. nigrum . The presence of such microorganisms is consistent with the findings of previous works, where the hydrolytic properties of isolates from historical objects or mummy‐related samples were investigated (Mesquita et al ., ; Kraková et al ., ; Naji et al ., ; Piñar et al ., ; Šimonovičová et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…This culture‐independent approach was also able to detect high abundances of other fungal taxa. Some of these have previously been isolated from mummified human remains, for example Aspergillus and Talaromyces, which also exhibited biodegradative potential (Naji et al ., ; Šimonovičová et al ., ). The occurrence of Metarhizium , an entomopathogenic fungus (Greenfield et al ., ), is likely associated with the presence of the different insects that colonized the mummified body.…”
Section: Discussionmentioning
confidence: 99%